Punches in the walls and slabs are being kept as per submitted drawing - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the punches of walls and slabs with work scope of supply, installation, testing and commissioning of substation, HT panel, LT panel and BBT system for BRACU new campus project.